Feeding behavior, life history, and virus transmission ability of Bemisia tabaci Mediterranean species (Hemiptera: Aleyrodidae) under elevated CO2. (20th March 2019) - Peñalver‐Cruz, Ainara; Garzo, Elisa; Prieto‐Ruiz, Inés; Díaz‐Carro, Miguel; Winters, Ana; Moreno, Aránzazu; Fereres, Alberto
Abstract: The continuous rise of CO2 concentrations in the atmosphere is reducing plant nutritional quality for herbivores and indirectly affects their performance. The whitefly ( Bemisia tabaci, Gennadius) is a major worldwide pest of agricultural crops causing significant yield losses. This study investigated the plant‐mediated indirect effects of elevated CO2 on the feeding behavior and life history of B. tabaci Mediterranean species. Eggplants were grown under elevated and ambient CO2 concentrations for 3 weeks after which plants were either used to monitor the feeding behavior of whiteflies using the Electrical Penetration Graph technique or to examine fecundity and fertility of whiteflies. Plant leaf carbon, nitrogen, phenols and protein contents were also analyzed for each treatment. Bemisia tabaci feeding on plants exposed to elevated CO2 showed a longer phloem ingestion and greater fertility compared to those exposed to ambient CO2 suggesting that B. tabaci is capable of compensating for the plant nutritional deficit. Additionally, this study looked at the transmission of the virus Tomato yellow leaf curl virus ( Begomovirus ) by B. tabaci exposing source and receptor tomato plants to ambient or elevated CO2 levels before or after virus transmission tests. Results indicate that B. tabaci transmitted the virus at the same rate independent of the CO2 levels and plant treatment. Therefore, we conclude that B. tabaci Mediterranean species prevails over the difficulties that changes in CO2 concentrations may cause and it is predicted that under future climate change conditions, B. tabaci would continue to be considered a serious threat for agriculture worldwide.